The Effect of a Modified GH11 Xylanase on Live Performance, Gut Health, and Clostridium perfringens Excretion of Broilers Fed Corn-Soy Diets - Nusairat, Basheer; Wang, Jeng-Jie (Frontiers in Veterinary Science, 2021)
Xylanase enzymes and other feed additives are being used more commonly in poultry feed to reduce feed cost, improve performance, and maintain gut health. Five corn-soy-based dietary treatments were designed to compare the effect of different inclusion levels of high-efficiency GH11 xylanase on live performance, gut lesions, and Clostridium perfringens excretion in littler samples of broiler chickens. Diets were the standard diet (positive control; PC); a diet of reduced energy by 130 kcal/kg diet (negative control; NC); NC with xylanase at 10 XU/g of feed (NC + 10); NC with xylanase at 12.5 XU/g of feed (NC + 12.5); NC with xylanase at 15 XU/g of feed (NC + 15). Data were analyzed with one-way ANOVA. At 42 d, birds fed NC + 12.5 and NC + 15 were heavier (P < 0.05) than NC and comparable improvement to birds fed PC. Significant Improvement in FCR (P = 0.0001) was observed from 1 to 42 d for NC + 12.5 and NC + 15 compared with NC. Supplementation of xylanase reduced (P < 0.005) 21 d intestinal lesion score at 21 d with further improvement (P < 0.0001) at 42 d. NC + 15 reduced lesion scores by 24% compared with NC. Xylanase supplementations reduced litter C. perfringens cell forming unit per gram (CFU/g) compared with NC with the highest reduction of NC + 15 treatment by ~27%. In conclusion, xylanase can be included in reduced-energy diets up to 15 XU/g of feed to improve live performance, energy digestibility, and reduce intestinal lesion scores in broilers.